Intramedullary Spinal Cord Tumors: Part I—Epidemiology, Pathophysiology, and Diagnosis. (October 2015) - Samartzis, Dino; Gillis, Christopher C.; Shih, Patrick; O'Toole, John E.; Fessler, Richard G.
Study Design: Broad narrative review. Objectives: Intramedullary spinal cord tumors (IMSCT) are rare neoplasms that can potentially lead to severe neurologic deterioration, decreased function, poor quality of life, or death. As such, a better understanding of these lesions is needed. The following article, part one of a two-part series, addresses IMSCT with regards to their epidemiology, histology, pathophysiology, imaging characteristics, and clinical manifestations. Methods: The authors performed an extensive review of the peer-reviewed literature addressing the aforementioned objectives. Results: Numerous IMSCT exist with varying epidemiology. Each IMSCT has its own hallmark characteristics and may vary with regards to how aggressively they invade the spinal cord. These lesions are often difficult to detect and are often misdiagnosed. Furthermore, radiographically and clinically, these lesions may be difficult to distinguish from one another. Conclusions: Awareness and understanding of IMSCT is imperative to facilitate an early diagnosis and plan management.